A novel strategy for stabilization of sub-nanometric Pd colloids on kryptofix functionalized MCM-41: nanoengineered material for Stille coupling transformation - Hassan Alamgholiloo (Nature Portfolio, 2021)
Abstract The stabilization of sub-nanometric metal particles (< 1 nm) with suitable distribution remained challenging in the catalytic arena. Herein, an intelligent strategy was described to anchoring and stabilizing sub-nanometric Pd colloids with an average size of 0.88 nm onto Kryptofix 23 functionalized MCM-41. Then, the catalytic activity of Pd@Kryf/MCM-41 was developed in Stille coupling reaction with a turnover frequency (TOF) value of 247 h−1. The findings demonstrate that porous MCM-41 structure and high-affinity Kryptofix 23 ligand toward adsorption of Pd colloids has a vital role in stabilizing the sub-nanometric particles and subsequent catalytic activity. Overall, these results suggest that Pd@Kryf/MCM-41 is a greener, more suitable option for large-scale applications and provides new insights into the stabilization of sub-nanometric metal particles.